2015
DOI: 10.4103/1119-3077.154208
|View full text |Cite
|
Sign up to set email alerts
|

Lipoatrophy among patients on antiretroviral therapy in Lagos, Nigeria: Prevalence, pattern and association with cardiovascular risk factors

Abstract: Lipoatrophy, though commonly encountered in patients on ART in Nigeria was not associated with the presence of dyslipidemia, abnormal FPG or hypertension. Regular monitoring by the physician and increased patients awareness are necessary to reduce its prevalence and impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[4] For example, the prevalence of hypertension in Nigeria among HIV-positive patients under anti-retroviral therapy ranges between 27%-41%. [5, 6] Thus, there is a strong need to reduce the burden of hypertension among PLHIV in Nigeria which requires the implementation of proven evidence-based interventions (EBIs) targeted at hypertension control in the region.…”
Section: Introductionmentioning
confidence: 99%
“…[4] For example, the prevalence of hypertension in Nigeria among HIV-positive patients under anti-retroviral therapy ranges between 27%-41%. [5, 6] Thus, there is a strong need to reduce the burden of hypertension among PLHIV in Nigeria which requires the implementation of proven evidence-based interventions (EBIs) targeted at hypertension control in the region.…”
Section: Introductionmentioning
confidence: 99%
“…It is defined by changes in adipose tissue and redistribution of fat from the periphery (face, buttocks, legs, arms) to the abdomen, neck, and breasts. Some studies have found that lipodystrophy is more common with dyslipidemia [29,[32][33][34], while some have not found a meaningful relation between dyslipidemia and lipodystrophy [35].…”
Section: Introductionmentioning
confidence: 99%